2016
DOI: 10.4103/0972-2327.186785
|View full text |Cite
|
Sign up to set email alerts
|

Intrasinus thrombolysis in cerebral venous sinus thrombosis: Experience from a university hospital, India

Abstract: Background:Intrasinus thrombolysis (IST) is believed to improve outcome in patients of cerebral venous sinus thrombosis (CVST) unresponsive to heparin.Purpose:The purpose of this article is to describe our experience with IST in patients of CVST unresponsive to heparin.Materials and Methods:Hospital databases were searched, and patients with CVST who underwent IST from May 2011 to March 2014 were identified. Data on clinical presentation, duration of symptoms, and indications and dosage of IST were retrieved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…CVT treatment is mainly supportive. Endovascular thrombolysis or surgical thrombectomy are reserved for patients with persistent or aggravated symptomatology, despite optimal anticoagulant therapy [ 11 ]. There are two phases for the anticoagulant treatment strategy: immediate treatment to prevent subsequent thrombotic events (a risk that may be prolonged for 3 months after the initial event), and secondary prophylaxis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…CVT treatment is mainly supportive. Endovascular thrombolysis or surgical thrombectomy are reserved for patients with persistent or aggravated symptomatology, despite optimal anticoagulant therapy [ 11 ]. There are two phases for the anticoagulant treatment strategy: immediate treatment to prevent subsequent thrombotic events (a risk that may be prolonged for 3 months after the initial event), and secondary prophylaxis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous real-world study, the incidence of recovery was observed 94% [ 10 ] in pregnancy-related group and 73.9% [ 11 ] in non-pregnancy-related women. Fifty-one patients in each group could achieve more than 80% power to a significance level of 0.05 2-tailed.…”
Section: Study Methodsmentioning
confidence: 99%